Evaluation of a teaching tool to increase the accuracy of pilot balloon palpation for measuring tracheostomy tube cuff pressure. (1st April 2013) - Jiang, Nancy; Del, Anthony G.; Iloreta, Alfred M.; Malkin, Benjamin D.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The purpose of this study was to evaluate the efficacy of a novel teaching tool to improve health care providers' ability to inflate tracheostomy tube cuffs to the appropriate pressure. Study Design Single‐blinded, randomized, controlled trial. Methods Subjects were randomized to a control and study group. The control group viewed a video about inflating tracheostomy tube cuffs to safe pressure levels. The study group viewed the same video and also got to palpate the pilot balloons of tracheostomy tube cuffs inflated to three different pressures. All subjects inflated tracheostomy tube cuffs to pressures they believed to be appropriate based on palpation of the pilot balloon preintervention, and immediately, 2 weeks, and 3 months postintervention. Results Forty‐nine health care providers participated in the study. There was no significant difference in the mean preintervention cuff inflation pressures between the two groups (36 cm H2O vs. 38 cm H2O, P = 0.4888), with both initially overinflating. Postintervention, the study group inflated the cuffs to significantly lower pressures than the control group, closer to the ideal of 25 cm H2O (26 cm H2O vs. 35 cm H2O, P = 0.0001). This difference was also observed 2 weeks (28 cm H2O vs. 37 cm H2O P <0.0001) and 3 months (28 cm H2O vs. 36 cm H2O, P = 0.0002) postintervention. Conclusions The novel teaching tool evaluated in this study is simple, easily reproducible, and low‐cost. Its use leads to long‐lasting improvement in health care providers' ability to more accurately inflate tracheostomy tube cuffs to safe pressures. Level of Evidence 1b. Laryngoscope, 123:1884–1888, 2013